A Dual Ka/Q-Band Reflectarray - S. V. Polenga; A. A. Erokhin; R. O. Ryazantsev; A. D. Poligina; R. M. Krylov; E. A. Litinskaya; E. R. Gafarov; A. M. Aleksandrin; Yu. P. Salomatov; I. Yu. Danilov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Duplex satellite communication is commonly arranged using two spaced frequency bands, with one band receiving and the other band transmitting signals to a satellite. The main task of a communications satellite antenna system consists in providing an identical coverage area across all involved frequency bands, which is often a challenging task for conventional parabolic reflector antennas. Reflectarrays allow an independent control of the reradiated wave phase in spaced frequency bands, which can be used to create efficient multi-band antenna systems for modern communication satellites.Aim. To develop a Ka/Q-frequency range phase-correcting element and to create on its basis a dual-band reflectarray for operation with orthogonal circular polarizations and identical gains in a given sector of angles in significantly spaced frequency ranges.Materials and methods. Numerical studies were carried out using the finite element analysis method. Radiation patterns were measured using the near field scanning method.Results. A single-layer dual-band phase-correcting reflectarray element was developed for operation with orthogonal circular polarizations with low losses and a weak dependence of the relative position of the elements on the phase characteristic. On the basis of the proposed element, a reflectarray consisting of 24 465 two-frequency elements was synthesized and manufactured. The developed prototype of a single-layer dual-band reflectarray demonstrated good characteristics, with the efficiency reaching 56 and 36 % in the Ka- and Q-frequency ranges, respectively, and an almost identical minimum gain in the ±0.75° angle sector.Conclusion. The research results confirm the potential of the developed reflectarray to successfully replace conventional parabolic reflectors installed both on modern communication satellites and as part of ground-based satellite terminals in the millimeter wavelength range.